Natural Agrobacterium Transformants: Recent Results and Some Theoretical Considerations - Chen, Ke; Otten, Léon (Frontiers in Plant Science, 2017)
Agrobacterium rhizogenes causes hairy root growth on a large number of plant species. It does so by transferring specific DNA fragments (T-DNA) from its root-inducing plasmid (pRi) into plant cells. Expression of T-DNA genes leads to abnormal root growth and production of specific metabolites (opines) which are taken up by the bacterium and used for its growth. Recent work has shown that several Nicotiana, Linaria, and Ipomoea species contain T-DNA genes from A. rhizogenes in their genomes. Plants carrying such T-DNAs (called cellular T-DNA or cT-DNA) can be considered as natural transformants. In the Nicotiana genus, seven different T-DNAs are found originating from different Agrobacterium strains, and in the Tomentosae section no <4 successive insertion events took place. In several cases cT-DNA genes were found to be expressed. In some Nicotiana tabacum cultivars the opine synthesis gene TB-mas2′ is expressed in the roots. These cultivars were found to produce opines. Here we review what is known about natural Agrobacterium transformants, develop a theoretical framework to analyze this unusual phenomenon, and provide some outlines for further research.